PERENCANAAN KAPASITAS PRODUKSI DENGAN PENDEKATAN BIAYA MARJINAL PADA PABRIK TAHU â€œSBRâ€ BENGKULU - Afifi Bachtiar (Universitas Prof. Dr. Hazairin SH, 2018)
Production capacity planning with a marginal cost approach and marginal sales proceeds to get the maximum profit at Bengkulu's